Influence of psychological contract on workplace bullying. (July 2018) - M., Rajalakshmi; B., Naresh
Abstract: A few decades back, organizations were very much targeted towards profit, productivity, performance and turnovers. But now some organizations are only concerned about their employee's well-being and satisfaction for better performance in their organization. In this esteem, researchers and organization are considering various factors which improve their employee satisfaction, employee well-being, employee productivity, employee morale, employee performance, employee behavior and attitude in the work environment. To increase this relationship between employee and employer, many scholars and management are focusing on various areas like, organizational justice, career satisfaction, employee Work Performance, employee and employer relationship in workplace, consequences of psychological contract, and effects of psychological contract on job outcomes and violation of psychological contract. Based on the many literature, there is a need for research on workplace bullying especially to know its impact is due to psychological contract violation in industries. Various researchers have undergone to know the behavior outcome of workplace bullying in other sectors like hospitality, service, IT Industry, etc. The purpose of this review research is to look at impact of psychological contract on workplace bullying among employees.